Development Of Novel Approach Rapid Multiplex Real-Time Loop-Mediated Isothermal Amplification (M-qLAMP) Assay For Detection Of Melioidosis Agent Burkhalderia Pseudomallei - Yean, Chan Yean (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
-